Tuning the thermoelectric properties of doped silicene nanoribbon heterostructures - González, K. A.; Núñez, C. D.; Orellana, P. A.; Rosales, L. (Frontiers in Physics, 2023)
In this work, we investigate the thermoelectrical properties of a silicene nanoribbon heterostructure composed of a central conductor fully doped with ad-atoms and connected to two pristine leads of the same material. Using a tight binding Hamiltonian, we have calculated the system's thermoelectric properties as a function of the geometrical confinement and external field. Our results exhibit an enhancement of the thermopower when a transverse electric field is applied to the conductor region for different temperatures. Besides, a violation of the Wiedemann-Franz law is observed around the ad-atom energy. Our results suggest that the thermoelectric properties of doped silicene nanoribbons can be efficiently tuned with external perturbations.